(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was carried out during the 2021 agricultural season at the Qarhata Research Station of the General Commission for Scientific Agricultural Research, with the aim of studying the response of 13 genotypes of sesame to water stress conditions applied during the flowering stage. The experiment was carried out according to a randomized complete block design (RCBD), in split-plot arrangement, in three replications. The results of the statistical analysis showed that there were significant differences (P≤0.05) in the traits of number of days until flowering, number of days until full maturity, plant height, and number of branches between the treatments, genotypes, and interaction effect. Water stress caused a significant decline in these traits, while the differences in the height of the first branch and the height of the first capsule weren’t significant. The genotypes also varied in their response to water stress conditions, as the two genotypes Hourani5 and Zuri4, achieved the lowest rates of decline in the average plant height and the highest rates of decline in the number of branches per plant, while the two genotypes, Zuri3 and Zuri con. showed the highest rates of decline in plant height. The Zuri2 genotype significantly increased the number of branches per plant, and there were no significant differences in the rates of decrease in the number of days to flowering and maturity in all genotypes.